Dewigged, bothered, and bewildered : British colonial judges on trial, 1800-1900 - McLaren, John, 1940- (Osgoode Society for Canadian Legal History series., 2011)
"Throughout the British colonies in the nineteenth century, judges were expected not only to administer law and justice, but also to play a significant role within the governance of their jurisdictions. British authorities were consequently concerned about judges' loyalty to the Crown, and on occasion removed or suspended those who were found politically subversive or personally difficult. Even reasonable and well balanced judges were sometimes threatened with removal. Using the career histories of judges who challenged the system, Dewigged, Bothered, and Bewildered illuminates issues of judicial tenure, accountability, and independence throughout the British Empire. John McLaren closely examines cases of judges across a wide geographic spectrum - from Australia to the Caribbean, and from Canada to Sierra Leone - who faced disciplinary action. These riveting stories provide helpful insights into the tenuous position of the colonial judiciary and the precarious state of politics in a variety of British colonies"--Provided by publisher.